Výroba tvárníku formy - Rosa, Jakub (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2017)
Smyslem diplomové práce je vytvoření náhradního tvárníku vstřikovací formy vhodnou metodou podle původního tvárníku tak, aby konečný výlisek splňoval požadované parametry povrchu. Práce je zaměřena na analýzu původního tvárníku a na experimentální ověření vhodných metod výroby ekvivalentu tvárníku.

The meaning of the diploma thesis is to create a new mold plunger for injection mold using a suitable method according to the original mold plunger. The final mold part should meet the required surface parameters. The work is focused on the analysis of the original mold plunger and the experimental verification of suitable methods of production of the equivalent mold plunger.
Production of the mold plunger
Keywords: Elektroerozivní obrábění; forma; tvárník; vstřikování plastů; textura; Electrical discharge machining; mold; mold plunger; injection molding; texture